The study of antioxcidant activity of caulerpa lentillifera and caulerpa racemose / Munirah Mohd Nor - Nor, Munirah Mohd (2020)
Oxidative stress is a dangerous condition which arises when there is imbalance between free radical and antioxidant rates which become one of the main concern worldwide due to its pathological effect. Antioxidant act as defense mechanism in body to protect biological areas from appearance of free radicals in cells. This study centralized on determining potential antioxidant activity of Caulerpa lentlillifera and Caulerpa racemosa extract through TPC, DPPH and FRAP assay. Percentage yield of these seaweeds extracts acquired was 20% using 95% ethanol as extraction solvent. Total phenolic content of Caulerpa racemosa and Caulerpa lentillifera extract at highest concentration of 100 μg/ml were at 443.34 ± 0.16 μg GAE/g and 394.08 ± 0.04 μg GAE/g, respectively. While, percentage scavenging activity of Caulerpa racemosa and Caulerpa lentillifera extract at 100 μg/ml were on 65.59% and 63.73%. At 100 μg/ml, FRAP value of Caulerpa racemosa and Caulerpa lentillifera extract were at 565.94 ± 0.03 μg AAE/g and 453.89 ± 0.05 μg AAE/g, respectively. Through all the tests that have been done in this study, both of the samples were seen to have a potential in health promoting product to fight the pathological effect of free radicals due to their antioxidant activity ability.